A Comparative Sustainable Assessment between Native Durian-Based Agroforestry System and Commercial Durian-Based Mixed Orchard in the Upstream of Ban Dan Na Kham Sub-district, Uttaradit Province - Boonyanuphap, Jaruntorn; Maosew, Kanchaya; Moolthasit, Pathamakorn; Suthampaeng, Thayut (Journal of Applied Informatics and Technology, 2021)
The current utilization of resources in the upstream areas of Ban Dan Na Kham, Sub district has changed by agriculturist changing the way of agriculture from a mixed fruit tree–based agroforestry that relies on the balance of nature to be agriculture that focuses on increasing commercial production that requires increasing chemical use in production. This has resulted in the environment impacts and cause of ecosystem degradation. This study aimed to assess the sustainability of the native durian-based agroforestry system compared with the commercial growing durian-based mixed orchard by using 17 sustainability indices. The sustainability indices were chosen and then classified in the basis of the four dimensions of sustainable developments, namely dimensions of household economic, social and cultural dimensions, local policy dimensions and environmental dimensions. The native durian-based agroforestry system has statistically significantly higher numbers of large forest tree and useful plant species, and amount of soil organic matter than the commercial growing durian-based mixed orchard (p<0.05). Assessment of the sustainability level under the current durian garden management system of both systems. In the overall, native durian under agroforestry system indicated a significantly higher percentage of total sustainability than the commercial mixed durian orchard (p=0.024), social and cultural dimensions and the environmental dimensions in particular. The local administrative organization can used this sustainability dataset on both durian-based production systems for planning the effective use of resources in upstream region including creating a public awareness program for the impact of changing agricultural way on the sustainable local development.